Mathematical Modelling of Kidnapping Activities - A. R. Tasiu; Kabir O; Aminu Muhammad; M. S. Ayu; M. M. Ishaq (Darul Yasin Al Sys, 2026)
Kidnapping has become one of the most severe security challenges in Nigeria, particularly in the northern regions, where it has evolved into a profitable criminal enterprise. This study develops a mathematical model to analyze the dynamics and control of kidnapping activities. The population is classified into five compartments: susceptible individuals, exposed individuals, informants, kidnappers, and repentant kidnappers. The model describes the transition of individuals from vulnerability to involvement as informants or kidnappers, as well as the possibility of repentance through rehabilitation. A basic reproduction number, (R_0), is derived to determine whether kidnapping activities will persist or decline. The analysis indicates that kidnapping can be eliminated when (R_0 < 1), whereas (R_0 > 1) implies its continued persistence. Numerical simulations further show that increasing the rehabilitation rate of kidnappers promotes repentance, while strengthening intelligence gathering through informants and reducing recruitment into kidnapping significantly suppress the expansion of this criminal activity. The study concludes that the proposed model provides useful quantitative insight into the mechanisms driving kidnapping and offers practical implications for policy interventions aimed at reducing kidnapping in Nigeria.